Apoptosis resistant bronchoalveolar lavage (BAL) fluid lymphocytes in sarcoidosis. Issue 10 (1st October 2002) - Stridh, H; Planck, A; Gigliotti, D; Eklund, A; Grunewald, J
Abstract : Background: Sarcoidosis is a chronic granulomatous lung disease of unknown origin. The accumulation of activated T cells at sites of inflammation represents an early stage in granuloma formation. Since mechanisms governing the normal resolution of inflammatory processes are poorly understood, this study aimed to investigate the apoptotic phenotype of peripheral blood and lung T lymphocytes from patients with sarcoidosis. Methods: Bronchoalveolar lavage (BAL) was performed in 10 patients with active sarcoidosis and five healthy controls. Results: Virtually no lymphocyte apoptosis, as determined by annexin V or Hoechst staining, was seen in either patients or controls. Sustained caspase-3 activity in non-apoptotic BAL fluid lymphocytes of the patients was detected, however, in agreement with in vitro studies demonstrating caspase activation after T cell receptor (TCR) triggering as a physiological response required for efficient T cell activation. Only 11.0% (range 7.7–17.6) of the BAL lymphocytes from sarcoidosis patients were annexin V positive after exposure to the apoptotic stimulus tributyltin compared with 55.0% (range 42.0–62.0) of BAL lymphocytes from healthy controls (p<0.001). After anti-Fas treatment only 8.5% (range 6–10) of BAL fluid lymphocytes from patients but 45.5% (range 38–62) from healthy controls were apoptotic. Conclusion: BAL fluid lymphocytes from patients with sarcoidosis display a non-apoptotic morphology associated with endogenous caspase-3 activity. They seem to be resistant to apoptosis, which might contribute to the accumulation of inflammatory cells in the lungs, persistence of inflammation, and the development and maintenance of granuloma.